2013
DOI: 10.2478/nsad-2013-0016
|View full text |Cite
|
Sign up to set email alerts
|

Accepted, desired and ashamed: Images of female alcohol use and drinking-related gender orders described by Finnish women of different ages

Abstract: Aims The article deals with how Finnish women of different ages perceive acceptable and desirable images of female alcohol use as well as gender orders associated with drinking. A focus on women and differences between women is motivated by the fact that women's increased drinking is one of the most significant changes in the Finnish alcohol landscape in recent history. Data and Design The data consists of group interviews with women aged 50–60, 35–40 and 25. The images of female alcohol use adopted in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…The analysis also showed that gendered evaluations of public intoxication seldom were expressed directly, indicating a norm of gender equality. This aligns with other recent studies concluding with a relaxation of gender stereotypes of alcohol use and intoxication in the Nordic countries (Abrahamson, 2012;Demant & T€ orr€ onen, 2011;Simonen, 2013). It is also possible that the focus group context gave ground for socially desirable statements, and that statements in favor of gender equality were regarded to be the most socially appropriate response.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The analysis also showed that gendered evaluations of public intoxication seldom were expressed directly, indicating a norm of gender equality. This aligns with other recent studies concluding with a relaxation of gender stereotypes of alcohol use and intoxication in the Nordic countries (Abrahamson, 2012;Demant & T€ orr€ onen, 2011;Simonen, 2013). It is also possible that the focus group context gave ground for socially desirable statements, and that statements in favor of gender equality were regarded to be the most socially appropriate response.…”
Section: Discussionsupporting
confidence: 89%
“…Recent research suggests that women's entry into public drinking spaces is one of the factors behind a change towards a more heterogenic and less intoxication-oriented drinking culture in these countries, and that women engaged in public drinking to a lesser extent than before provoking negative and immoral images (Demant & T€ orr€ onen, 2011). It has also been suggested that women's gender identity in relation to drinking has expanded beyond traditional feminine values and become more layered and varied (Simonen, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors together with poorer language proficiency as an indicator for lower acculturation were all protective factors against binge drinking among Kurdish women. The gender differences in the drinking patterns of Kurdish migrants were reminiscent of the gender differences in drinking patterns in the Finnish population some decades ago; nowadays, this has dissolved with the alarming increase in the alcohol consumption of Finnish women and the simultaneous significant gender role changes in Finnish society [ 65 , 66 ]. The prevalence of abstainers has decreased and the proportion of weekly drinkers has increased among Finnish women between 1968 and 2008 [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…This norm refers to the notion that women should only engage in sexual activity within a monogamous relationship . Given that the sexual fidelity norm is reflective of traditional attitudes, perhaps women who endorse this norm may feel that excessive alcohol consumption may jeopardize their romantic relationships, and are thus less likely to engage in HED (Simonen, 2013). Moreover women who endorse the sexual fidelity norm do not feel the need to engage in HED to facilitate their social interactions with men (Young et al, 2005).…”
Section: Data Analytic Planmentioning
confidence: 99%